Peningkatan Keterampilan Menulis Karangan Eksposisi Dengan Menerapkan Metode Demonstrasi Pada Peserta Didik Kelas VIA SDI Bhonawa 1 - Maria Goreti Sri Kusumastuti (Ekspektasi: Jurnal Pendidikan Ekonomi, 2020)
This study aims to determine: (1) the application of the method to the exposition writing material in Indonesian language learning in class VIA SDI Bhonawa1 (2). Increasing the ability to write exposition essays in Indonesian language learning after going through the demonstration method in class VIA SDI Bhonawa students 1. This type of research is Classroom Action Research (CAR). While the approach used is a qualitative approach. The research design carried out by the author in this study followed the class action research design pattern of Kemmis and Mc. Taggart, with research procedures namely pre-action and action. Actions are carried out in four stages, planning, implementing, observing and reflecting. The research subjects were students of class VIA SDI Bhonawa 1, totaling 20 students. Observation data collection techniques, interviews and tests. The results of the study were as follows, in the pre-action the number of students who completed or fulfilled the KKM was only 5 students, in cycle I increased to 9 students and in cycle II increased to 20 students. Based on this change, pre-action classical completeness was 33.3%, cycle I classical completeness was 46.6% and cycle II was 100%.